Wykorzystanie outsourcingu jako metody wspomagającej zarządzanie procesowe (na przykładzie przedsiębiorstw województwa podkarpackiego) - Ujda-Dyńka, Beata; Zych, Anna (Taking the Advantage of Outsourcing as a Method Helping Process Management (Examples of the Companies of Voivodship of Podkarpacie), 2009)
The article is aimed at presenting the research associated with the use of outsourcing in the companies of voivodship of Podkarpacie. Outsourcing as a method helping process management is observed when a company or an organization employs another company to do its work and the employed company is indirectly connected with a certain company. It should lead to the better fulfillment of economic purposes.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 215-220